Industry 4.0 and the impact of technology on the future of work: A qualitative approach to the IT jobs - Ion Moldoveanu (CES Working Papers, 2022)
Scientific research leads the scientific progress based on which information technology (I.T.) professionals drive technology changes, impacting our daily life, business, and work models. The same inventions are impacting the work of the software developers, the ones responsible for building this technology. While I.T professionals are building new tools for automation used in the industry, the work of I.T. professionals is significantly impacted by the tools they build. Paying heed to these considerations, the paper intends to bring forward qualitative research based on semi-structured interviews with 18 I.T. professionals. The research purpose is to scrutinize to what extent the workers in the software development industry are aware of the transformations happening in their profession, how they see the future of their jobs and how they prepare for that future. The I.T. engineers taking part in the interviews see the impact of technology in changing their work models, making them more productive rather than a threat to their jobs. They also understand the importance of continuous learning, keeping up with technological changes and soft skills.
Keywords: 330; industry 4.0; technology; automation; future of work; IT jobs